EFL Teachers Engagement in Reflective Practice: What tools do EFL teachers utilize to reflect their teaching? - Tosriadi, Tosriadi; Asib, Abdul; Marmanto, Sri (Universitas Muhammadiyah Semarang, 2018)
This study was aimed at reviewing some reflective practice tools utilized by EFL teachers in reflecting their classroom performance as an attempt to improve their teaching. 4 English teachers with teaching experience ranging from 7-24 years were involved in this study. Data were collected through interview, observation, and document analysis. The result of data analysis informed some individual differences among EFL teacher?s preference in doing reflection over their teaching. Basically, there are 4 tools utilized by respondents to evaluate their teaching; learning journal, students? feedback, peer observation, and action research. It is shown the role of reflective practice in teacher development is very vital.